A new species of miniature catfish from the Malay Peninsula (Teleostei: Bagridae: Nanobagrus) - Ng, Heok Hee (Zootaxa, 2010)
Nanobagrus lemniscatus, a new species of miniature bagrid catfish from the Malay Peninsula is described here. It can be distinguished from congeners in having the following combination of characters: large cream patches on a brown body frequently coalescing to form broad transverse band, length of adipose-fin base 24.0–27.1% SL, body depth at anus 13.1–14.0% SL, 35–36 vertebrae, pectoral spine with length 16.1–18.7% SL and 7–9 serrations on its posterior margin, and a convex neurocranium. Nanobagrus stellatus is also recorded from the Malay Peninsula for the first time in this study.